Inhibition of HMG-CoA Reductase Activity by Kersen Leaves (Muntingia calabura L.) to Prevent Hypercholesterolemia: Inhibisi HMG-CoA Reduktase Menggunakan Ekstrak Daun Kersen (Muntingia calabura L) Untuk Mencegah Hiperkolesterolemia - Tien Tien; Nishar Rakhman Ardiansyah; Carla Wulandari Sabandar; Laode Kardin; Pranita Aritrina (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Hypercholesterolemia is a condition of total cholesterol level >200 mg/dL and LDL >130 mg/dL. HMG-CoA (3-hydroxy-3-ethylglutaryl-coenzyme A) reductase is an enzyme that has a role in cholesterol biosynthesis. Hence, inhibition of this enzyme led to the decrement of cholesterol level. The extract of Kersen leaves (Muntingia calabura L.) is known to contain flavonoids, terpenoids, steroids, tannins, phenolic, and alkaloids. Flavonoids work by inhibiting the HMG-CoA reductase activity, so that mevalonate cannot be formed and thus decrease the cholesterol synthesis. Objectives: The present study aimed to determine the effect of Kersen leaves extract (M. calabura L.) in inhibiting the HMG-CoA reductase activity in vitro. Material and Methods: The study is a true experimental study with a post-test-only control group design. The independent variables were ethanol, methanol, and n-hexane extracts of Kersen leaves. Moreover, the percentage inhibition of the enzyme was the dependent variable. The test was conducted in vitro using UV-Vis spectrophotometry with pravastatin as a positive control. Results: The inhibitory effects of ethanol, methanol, n-hexane extracts of Kersen leaves, and pravastatin towards HMG-CoA reductase activity were 85.56%, 59.75%, 92.03%, and 99.58%, respectively. Post Hoc One-Way ANOVA showed that the p-values of pravastatin with ethanol, methanol, and n-hexane extracts were 0.687, 0.048, and 0.931, respectively. The n-hexane and ethanol extracts were potent for inhibiting the enzyme activity (p>0.05) comparable to pravastatin. Conclusion: The n-hexane and ethanol extracts of Kersen leaves could serve as a natural source of HMG-CoA reductase inhibitor to prevent hypercholesterolemia.